PENGARUH RETURN ON ASSET (ROA), BOOK VALUE EQUITY PER SHARE (BV), DEBT TO EQUITY RATIO (DER), VOLUME PERDAGANGAN SAHAM DAN INDEKS HARGA SAHAM TERHADAP HARGA SAHAM BANK MNC DI BURSA EFEK INDONESIA PERIODE 2014 – 2021 - Calvin Pandu Wicaksana; Aprilia Dian Evasari; Diana Ambarwati (Commodities, Journal of Economic and Business, 2022)
The type of research used in this research is quantitative. The results of research conducted by researchers (1) Return On Assets have no partial effect on the MNC BANK Share Price on the Indonesia Stock Exchange for the 2014 – 2021 period. (2) Book Value Equity Per Share has no partial effect on the MNC BANK Share Price on the Stock Exchange Indonesian Securities Period 2014 – 2021. (3) Debt To Equity Ratio has no partial effect on the Share Price of MNC BANK on the Indonesia Stock Exchange for the 2014 – 2021 Period. (4) Stock Trading Volume has no partial effect on the Share Price of MNC BANK on the Stock Exchange Indonesia Period 2014 – 2021. (5) The Stock Price Index has no partial effect on the MNC BANK Share Price on the Indonesia Stock Exchange for the 2014 – 2021 Period. Simultaneous Test Calculation (Test F) can be concluded that H0 is accepted and Ha is rejected, which means Return On Assets , Book Value Equity Per Share, Debt To Equity Ratio, Stock Trading Volume and Stock Price Index do not simultaneously affect the share price of MNC BANK on the Indonesia Stock Exchange for the 2014 – 2021 period.